WMJ-S-001, a Novel Aliphatic Hydroxamate-Based Compound, Suppresses Lymphangiogenesis Through p38mapk-p53-survivin Signaling Cascade - Huang, Shiu-Wen; Yang, Hung-Yu; Huang, Wei-Jan; Chen, Wei-Chuan; Yu, Meng-Chieh; Wang, Shih-Wei; Hsu, Ya-Fen; Hsu, Ming-Jen (Frontiers in Oncology, 2019)
Background and purpose: Angiogenesis and lymphangiogenesis are major routes for metastatic spread of tumor cells. It thus represents the rational targets for therapeutic intervention of cancer. We recently showed that WMJ-S-001, a novel aliphatic hydroxamate-based compound, exhibits anti-inflammatory, anti-tumor, and anti-angiogenic properties. However, whether WMJ-S-001 is capable of suppressing lymphangiogenesis and its underlying mechanisms remain unclear. In this study, we explored WMJ-S-001’s anti-lymphangiogenic mechanisms in lymphatic endothelial cell (LECs). Experimental approach: WMJ-S-001’s effects on LEC proliferation, migration, and invasion, as well as signaling molecules activation, were analyzed by immunoblotting, flow-cytometry, MTT, BrdU, migration and invasion assays. We performed the tube formation assay to examine WMJ-S-001’s ex vivo anti-lymphangiogenic effects. Key results: WMJ-S-001 inhibited serum-induced cell proliferation, migration, invasion in murine LECs (SV-LECs). These results are associated with the reduction of survivin mRNA and protein levels. Survivin knockdown significantly suppressed the serum-induced SV-LEC invasion. WMJ-S-001 caused increases in p53 phosphorylation and its reporter activities. Sp1 binding to the survivin promoter region decreased while p53 binding to the promoter region increased after WMJ-S-001 exposure in SV-LECs. WMJ-S-001 activated p38 mitogen-activated protein kinase (p38MAPK). Blockade of p38MPAK signaling significantly inhibited p53 phosphorylation in WMJ-S-001-stimulated SV-LCEs. Furthermore, WMJ-S-001 induced survivin reduction and inhibited serum-induced cell proliferation, invasion and tube formation of primary human LECs. Conclusions and Implications: Together, these results indicate that WMJ-S-001 may inhibit lymphatic endothelial remodeling and suppress lymphangiogenesis through the p38MAPK-p53-survivin cascade. These results also support the role of WMJ-S-001 as a potential lead compound and warrant clinical development in the treatment of lymphangiogenesis-associated diseases and cancer.